High sensitivity refractive index sensing with good angle and polarization tolerance using elliptical nanodisk graphene metamaterials. (29th May 2019) - Huang, Jing; Niu, Gao; Yi, Zao; Chen, Xifang; Zhou, Zigang; Ye, Xin; Tang, Yongjian; Yi, Yong; Duan, Tao; Yi, Yougen
Abstract: In this paper, we theoretically propose a high sensitivity refractive index metamaterial sensor, which is composed of four semi-elliptic nanodisk graphene structure. This periodic structure has high tolerance of operating angles (0°–60°) and can be turned. According to our numerical calculations, the sensitivity of sensor is up to 11.5 μ m/RIU and the figure of merit is 3.9. The proposed sensor achieves dynamic tuning mainly through the doping concentration of graphene. Our proposed sensor is simple in structure, low cost and can achieve dual-band sensing by simple arrangement. Its high sensitivity can easily meet the requirements of high precision detection of gas and liquid refractive index.